Advancing Traditional Leadership Theories by Incorporating Multicultural and Workforce Diversity Leadership Traits, Behaviors, and Supporting Practices: Implications for Organizational Leaders - Scott, Chaunda L.; Klein, Laura B. (Journal of Leadership, Accountability and Ethics, 2022)
Well-known and respected traditional leadership theories such as Transformational Leadership Theory (Bass 1985, 1989, Authentic Leadership Theory (Luthans & Avolio 2003), and Distributed Leadership Theory (Lumby, 2013) offer insight into the ways that leadership can be applied and practiced in various organizational contexts. These traditional leadership theories are known for underscoring the kinds of traits and behaviors that prospective and current leaders should possess to enhance their leadership abilities and overall effectiveness. However, one area that is absent from traditional leadership theories is a focus on the kinds of multicultural and workforce diversity leadership knowledge, skills, and abilities that organizational leaders should possess to manage human diversity effectively in a variety organizational setting. The aim of this paper is to: 1) summarize the role of three well-known traditional leadership theories; 2) share examples of existing multicultural and workforce diversity frameworks that offer insights for advancing traditional leadership theories; and 3) highlight the benefits of incorporating multicultural and workforce diversity leadership traits, behaviors and supporting diversity practices into traditional leadership theories.